The Commitment Paradox: Aligning Employee Well-being and Organizational Productivity in the Era of Quiet Quitting - Aldi Adi Pratama (Universitas Teknologi Surabaya, 2025)
The phenomenon of quiet quitting has emerged as a significant challenge in modern human resource management, reflecting a fundamental shift in the psychological contract between employers and employees. This study aims to explore integrative strategies capable of aligning employee well-being with organizational productivity targets to address the commitment paradox. Utilizing a descriptive qualitative approach, this research integrates the Job Demands-Resources (JD-R) model and the Conservation of Resources (COR) theory to analyze the psychological processes of employee withdrawal as a protective mechanism against emotional exhaustion or burnout. The analysis indicates that quiet quitting is characterized by minimal work effort, low emotional investment, and restricted social communication. Demographic factors, such as age (Generation Z) and organizational injustice, serve as the primary drivers of this phenomenon. The study concludes that organizations must recalibrate managerial strategies through transformational leadership, the provision of autonomy via job crafting, and the strengthening of psychological safety to foster a sustainable work ecosystem